Marketing aspects of forming the strategy of financial and economic security of enterprises - Tarasiuk, Halyna (Public Policy and Accounting, 2024)
The importance of the use of marketing tools in the formation of a strategy for ensuring the financial and economic security of enterprises in the conditions of an unstable environment and rapid globalization changes has been investigated and substantiated. The expediency of using innovative approaches in the formation of marketing strategies has been proven. Innovative marketing strategies should include the use of advanced technologies, creation of unique products, active participation in social marketing, personalization of interaction with customers and flexible adaptation strategies. The improvement of conceptual approaches to the scientific knowledge of the theory of financial and economic security of the enterprise consists in the application of a systemic and communicative paradigm, taking into account the synergistic effect of the studied phenomenon based on the theoretical approaches of the theory of systems, management, information, and mathematical modeling, which are the basis for the development of multivariate approaches to solving current problems of fifinancial and economic security of the enterprise. It is suggested to use different strategies to expand your market, such as: development of new products or services, diversification of the offer, opening of new geographical territories or targeting new segments, which will allow you to maintain financial stability and ensure long-term financial and economic security of the business.